Pengaruh Pembiayaan Ar-Rahn, Pembiayaan Ar-Rum, Harga Emas, dan Covid-19 terhadap Laba PT Pegadaian Syariah Indonesia Periode 2020-2022 - Ani Kurniawati; Moh. Mukhsin; M. Ainun Najib (Jurnal Masharif al-Syariah: Jurnal Ekonomi dan Perbankan Syariah, 2024)
This research was conducted to find out how Rahn's financing affects PT Pegadaian Syariah Indonesia's company profits, how does Arrum's financing affect PT Pegadaian Syariah Indonesia's profits, how does the amount of gold price affect PT Pegadaian Syariah Indonesia's profits, how does Covid-19 affect company profits PT Pegadaian Syariah Indonesia, How does Financing Rahn, Financing Arrum, Gold Prices, Covid-19 simultaneously affect the company's profits PT Pegadaian Syariah Indonesia. This study uses a quantitative method and uses secondary data obtained from the OJK website. The data analysis method in this study uses multiple linear analysis methods. The results showed that partially Rahn had a positive effect on pawnshop profit. partially Arrum has an effect on pawnshop profit prolehan. Gold prices have no effect on pawnshop profits, Covid-19 has no effect on pawnshop profits. Rahn, Arrum, the price of gold, covid-19 together (simultaneously) have a significant effect on Profit Gains from Islamic Pawnshops for the 2020-2022 period. Key words: Rahn Financing, Arrum, Gold Price, Covid-19, Company Profits.